Stabilizing the Li1.3Al0.3Ti1.7(PO4)3|Li Interface for High Efficiency and Long Lifespan Quasi‐Solid‐State Lithium Metal Batteries. Issue 10 (22nd April 2022) - Chen, Zhen; Stepien, Dominik; Wu, Fanglin; Zarrabeitia, Maider; Liang, Hai‐Peng; Kim, Jae‐Kwang; Kim, Guk‐Tae; Passerini, Stefano
Abstract: To tackle the poor chemical/electrochemical stability of Li1+ x Al x Ti2‐ x (PO4 )3 (LATP) against Li and poor electrode|electrolyte interfacial contact, a thin poly[2, 3‐bis(2, 2, 6, 6‐tetramethylpiperidine‐ N ‐oxycarbonyl)norbornene] (PTNB) protection layer is applied with a small amount of ionic liquid electrolyte (ILE). This enables study of the impact of ILEs with modulated composition, such as 0.3 lithium bis(fluoromethanesulfonyl)imide (LiFSI)‐0.7 N ‐butyl‐ N ‐methylpyrrolidinium bis(fluoromethanesulfonyl)imide (Pyr14 FSI) and 0.3 LiFSI‐0.35 Pyr14 FSI‐0.35 N ‐butyl‐ N ‐methylpyrrolidinium bis(trifluoromethanesulfonyl)imide (Pyr14 TFSI), on the interfacial stability of PTNB@Li||PTNB@Li and PTNB@Li||LiNi0.8 Co0.1 Mn0.1 O2 cells. The addition of Pyr14 TFSI leads to better thermal and electrochemical stability. Furthermore, Pyr14 TFSI facilitates the formation of a more stable Li|hybrid electrolyte interface, as verified by the absence of lithium "pitting corrosion islands" and fibrous dendrites, leading to a substantially extended lithium stripping‐plating cycling lifetime (>900 h). Even after 500 cycles (0.5C), PTNB@Li||LiNi0.8 Co0.1 Mn0.1 O2 cells achieve an impressive capacity retention of 89.1 % and an average Coulombic efficiency of 98.6 %. These findings reveal a feasible strategy to enhance the interfacial stability between Li and LATP by selectively mixing different ionic liquids. Abstract : Incorporating a small amount of ionic liquid electrolyte (0.3LiFSI‐0.35Pyr14 FSI‐0.35Pyr14 TFSI) within a hybrid electrolyte that also contains Li1.3 Al0.3 Ti1.7 (PO4 )3 (LATP) and the polymer PVDF‐TrFE yields drastically enhances interfacial stability against lithium metal, prolonging the lithium stripping‐plating lifetime by a factor of 3.7 and giving superior cycling stability over 500 cycles (0.5C) in full cells with LiNi0.8 Co0.1 Mn0.1 O2 (NCM811 ) as the cathode material.